2022
DOI: 10.1210/clinem/dgac695
|View full text |Cite
|
Sign up to set email alerts
|

Association of Longitudinal Activity Measures and Diabetes Risk: An Analysis From the National Institutes of Health All of Us Research Program

Abstract: Aims Prior studies of the relationship between physical activity and incident type 2 diabetes mellitus (T2DM) relied primarily on questionnaires at a single time point. We sought to investigate the relationship between physical activity and incident T2DM with an innovative approach using data from commercial wearable devices linked to electronic health records in a real-world population. Methods Using All of Us participants’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Evidence supports that 5000 steps or more per day may reduce mortality compared to 2700 steps per day [ 127 ]. Among those who engage in over 10,000 steps per day, the risk of incident type 2 diabetes mellitus (T2DM) is substantially reduced [ 128 ]. The health benefits of increasing steps per day appear to be linear up to 10,000 steps per day, with each 2000-step increment above inactivity associated with 6% lower risk of progression toward T2DM [ 129 ].…”
Section: Etiology Diagnosis and Treatmentmentioning
confidence: 99%
“…Evidence supports that 5000 steps or more per day may reduce mortality compared to 2700 steps per day [ 127 ]. Among those who engage in over 10,000 steps per day, the risk of incident type 2 diabetes mellitus (T2DM) is substantially reduced [ 128 ]. The health benefits of increasing steps per day appear to be linear up to 10,000 steps per day, with each 2000-step increment above inactivity associated with 6% lower risk of progression toward T2DM [ 129 ].…”
Section: Etiology Diagnosis and Treatmentmentioning
confidence: 99%
“…52 Another systematic review compared types of datasets and demonstrated better predictive utility of EMR data compared with administrative data, but noted that most studies failed to include socioeconomic predictors or metrics of model calibration, and did not consider clinical implications. 53 With the growth of available data sources for research (eg, All of Us, UK Biobank), [54][55][56] EMR data for these applications will only continue to grow. The Work Group considered all available data sources and reviewed the advantages and challenges of each and judged that the inclusion of EMR data in the derivation and validation datasets would be highly innovative, and would, on balance, enhance the predictive utility and generalizability of newly developed risk prediction equations.…”
Section: B-nrmentioning
confidence: 99%
“…85 An analysis from the All of Us Research Program utilizing longitudinal measures of physical activity from commercial wearable devices reported an association between higher levels of physical activity and a lower risk of incident diabetes. 108 Analyses from CARDIA have suggested that physical activity in young adulthood with maintenance into middle adulthood may reduce incident hypertension and prevent premature cardiovascular events in middle-aged adults. 109 Reduction in heart failure risk with physical activity may be most effective in persons without established atherosclerotic disease.…”
Section: Middle Adulthood (45-64 Years)mentioning
confidence: 99%